Major Amputation Profoundly Increases Mortality in Patients With Diabetic Foot Infection - Vuorlaakso, Miska; Kiiski, Juha; Salonen, Tapani; Karppelin, Matti; Helminen, Mika; Kaartinen, Ilkka (Frontiers in Surgery, 2021)
Introduction An acute diabetic foot infection (DFI) is a serious condition and a leading cause of hospitalization and major amputation in patients with diabetes. Aim of this study was to evaluate the long term survival and risk factors for death and amputation after the DFI requiring hospital treatment. Materials and methods A retrospective study included all adult patients hospitalized for DFI treatments during 2010-2014. Overall survival (OS) and amputation free survival (AFS) (without major amputation) was calculated. We performed a Cox regression analysis of several clinical parameters to evaluate the effects of clinical parameters on overall and amputation-free survival. Results Total of 324 patients with mean age of 66.8 (SD 12.8) years were included. The one- and five-year OS after DFI 81.2% (95%CI 77.5-84.9%) and 49.7% (95%CI 44.8-54.6%), respectively. Major amputation, wound ischemia, older age, and a low glomerular filtration rate reduced the OS after DFI. After a major amputation, the one- and five-year OS was 41.7% (95%CI 13.9-69.5) and 8.3% (95%CI 0.0-24.0%), respectively. Wound ischemia, older age, and elevated C-reactive protein reduced AFS. In contrast, hypertensive medication use was identified as a protective factor. Conclusion Mortality after a DFI remains high and is significantly increased after a major amputation. Findings highlight the importance of early wound and ischemia management for DFI prevention.